Medicine Shortages in Serbia: Pharmacists' Standpoint and Potential Solutions for a Non-EU Country - Nataša Jovanović Lješković; Aleksandra Jovanović Galović; Svetlana Stojkov; Nikola Jojić; Slobodan Gigov (MDPI AG, 2021)
Medicine shortages in Serbia have evidently been present for several decades, but literature data are scarce. The aim of our study was to get an insight on the present situation in Serbia, review the EU actions when managing shortages, and discern a set of potential measures. A short survey was conducted among 500 pharmacists in public pharmacies, in 23 cities in Serbia. The survey questions addressed frequency of drug shortages, professional actions in the event of shortages, main consequences to patients and pharmacies, putative causes, and pivotal measures for the prevention/mitigation of drug shortages under current conditions. Moreover, a Panel of Experts was organized, whose suggestions and opinions were used to analyze the present situation and to form a set of potential solutions and effective measures to mitigate shortages of medicines. In-depth analysis of current Serbian legislation was conducted, with emphasis on specific steps to be made within the actual legal framework. Examples of good practice in the EU, applicable to a country such as Serbia, were examined. Our research showed that although Serbia is, in some aspects, behind EU countries regarding the approaches to overcome medicine shortages, progress can be made within short period of time, by specific well-targeted actions. Both patients and pharmacists would benefit from it.